The effect of high dose vitamin C and E supplementation on VO2max, hemoglobin mass and endurance performance in well trained subjects - Holden, G.; Landgraf, H.; Raastad, T.; Hallén, J.; Paulsen, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The effect of high dose vitamin C and E supplementation on VO2max, hemoglobin mass, and endurance performance in well trained subjects Holden, Geir., Landgraff, Hege., Raastad, Truls., Hallén Jostein., and Paulsen, Gøran. Norwegian School of Sport Sciences, Oslo, Norway Introduction There is a widespread use of antioxidant supplementation in general population and among athletes. A growing body of evidence indicates detrimental effects of high-dose antioxidant supplementation on health and performance benefits of training (Gomez-Cabrera et al., 2008). The aim of this study was to investigate the effects of high-dose of antioxidant supplementation (vitamin C and E) during an 11 week endurance training regiment on maximal oxygen consumption (VO2max), running performance (beep-test; 20m shuttle run), blood volume (BV) and total hemoglobin mass (HbM), as well as oxygen consumption (VO2), heart rate (HR) and blood lactate concentration (La) on submaximal performance on motorized treadmill. Methods: Seventeen endurance trained subjects (12 females and 5 males; age: 24.4±2.9 yrs, VO2max 55.0±7.9 (ml/kg/min) were recruited and randomized in an antioxidant group (AG) and a placebo group (PG). The AG (n=8) received 1000 mg vitamin C and 235 mg vitamin E daily, while the PG (n=9) received placebo pills. The study was a double blinded design. The training protocol consisted of 3-4 endurance training sessions every week for 11 weeks, combining interval (4 x 4 up to 6 x 6min; > 90% HRmax) and continuous running sessions (30 and 60 min; ~85% HRmax and ~75% HRmax), respectively. The subjects were tested before and after 5 and 11 weeks of training and supplementation. Results: VO2max increased by 8.9±2.9% in AG and by 7.8±4.0% in PG (p<0.01). PG significantly reduced HR at a workload corresponding to 60% of initial VO2max test by 4.4±4.6% (p=0.02), while AG had a small increase in HR by 1.3±3.1% (p=0.3). At a workload of 85% of initial VO2max, PG significantly reduced HR by 4.7±5.0% (p=0.02), with AG increasing HR by 1.6±3.1% (p=0.3 within and p=0.01 between groups). There were no significant changes in blood (La) at the submaximal workloads for either group. Performance in the beep-test did not change significantly in AG 3.4±8.2% (p=0.3), but improved distance in PG by 14.3±14.1% (p=0.02). No significant changes were observed for BV or HbM in the two groups. Discussion: The 11 week endurance training program increased VO2max in both AG and PG, with no changes in BV or HbM. Supplementation with large doses of vitamin C and E hindered the training induced reduction in HR at submaximal workloads. Even though there were no group differences in performance changes in the beep-test, only the PG increased significantly their performance. Our results suggest that antioxidant supplementation may hamper endurance training induced adoptions related to performance.